ANALISIS STRATEGI PENGELOLAAN PASAR JOHAR OLEH DINAS PASAR KOTA SEMARANG - Bekti Rahayu; R. Slamet Santoso; Maesaroh Maesaroh (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
The existence of traditional markets is one of the most real indicators of economic activities in an area. Johar condition is still bad because there are no supporting facilities and unadequate comfort factor. The aim of this research is to formulate a strategy that must be done by the Market Service of Semarang to improve the management of Johar Market. This research used a qualitative descriptive study. The techniques of collecting data is from the result of the interview. This study used purposive sampling method to determine the informants. The writer identified the internal and external factors by using SWOT analysis, then will be gained strategic issues. The next step is measuring the priority scale by doing litmus test to know the most strategic issue. The results of this research showed that Johar market management strategy has not been optimal yet in solving the existing problems. so we need a new strategy. The recommended strategy is to improve the function and role of stakeholders in developing the potential of Johar market especially in competitiveness , develop the cooperation with government / private sector to improve infrastructure service, improve the coordination between the Market Service, Government, UPTD, and sellers to make renovation of buildings and infrastructure based on the rules from the government, develop cooperation with the government and private sectors to solve the lack of budget, and cooperate with sellers in the arrangement to solve the lack of capacity.